Validitas Modul Berbasis Pendekatan Saintifik Tentang Materi Sistem Gerak Untuk SMA - Fuji Zahara Zahara; Ardi Ardi; Helendra Helendra; Yusni Atifah; Meilani Syaiful (JURNAL PENDIDIKAN ROKANIA, 2022)
Learning media is a tool that can help the teaching and learning process and serves to clarify the meaning of the message conveyed, so as to achieve better and more perfect learning objectives. One of the learning media that can be developed is the learning module.Modules are teaching materials that are completely designed to help students learn independently. Module development must be in accordance with the implementation of the 2013 Curriculum learning, namely the scientific approach or scientific approach. Scientific approach-based modules can provide understanding to students in recognizing, understanding various materials using a scientific approach, learning is directed to encourage a scientific approach to find out from various sources through observation, not just given by the teacher. This study aims to produce a module based on a scientific approach about motion system material and to determine the level of validity of the module. This type of research is research and development. This study will use three stages of the 4-D development model, namely the stage of defining, designing and developing. The module was validated by 3 validators, namely two biology lecturers, FMIPA UNP and 1 biology teacher at SMAN 1 Pantai Cermin using an instrument in the form of a validity sheet. The results of the validity show that the module based on a scientific approach on the motion system material is declared to be very valid after being validated by 3 validators with an average percentage of 85.72% with a very valid category